PERAN FILSAFAT ILMU DALAM PEMBELAJARAN PENDIDIKAN PANCASILA PADA SISWA KELAS II DI SDN 136 PALEMBANG - Putri Widya Wati; Yulita Devi Utami; Tiara Munggarani; Aji Dwi Nugraha; Alya Samsida; Darwin Effendi; Hasperi Susanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The teaching of Pancasila Education at SDN 136 Palembang faces significant challenges because the presentation of the material remains theoretical and tends to be boring. This has led to low student participation and a lack of understanding among second-grade students regarding character values such as caring attitudes and the culture of waiting in line. This study aims to examine the role of the philosophy of science as a tool for creating more meaningful learning through the foundations of ontology, epistemology, and axiology. The method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through the stages of reduction, presentation, and drawing conclusions. The results of the study indicate that the application of the philosophy of science through careful planning and the use of concrete media is highly effective in shaping students’ character. Although there were challenges due to differences in students’ comprehension levels, a patient approach and the use of simple language were able to transform abstract material into concrete actions. Ultimately, students did not merely memorize theories but successfully understood the logical benefits of the values of honesty and harmony in their daily school life